Azetidine-based selective glycine transporter-1 (GlyT1) inhibitors with memory enhancing properties. Issue 14 (15th July 2020) - Hudson, Andrew R.; Santora, Vincent J.; Petroski, Robert E.; Almos, Theresa A.; Anderson, Gary; Barido, Richard; Basinger, Jillian; Bellows, Chris L.; Bookser, Brett C.; Broadbent, Nicola J.; Cabebe, Clifford; Chai, Chih-Kun; et al.
Graphical abstract: Abstract: A strategy to conformationally restrain a series of GlyT1 inhibitors identified potent analogs that exhibited slowly interconverting rotational isomers. Further studies to address this concern led to a series of azetidine-based inhibitors. Compound 26 was able to elevate CSF glycine levels in vivo and demonstrated potency comparable to Bitopertin in an in vivo rat receptor occupancy study. Compound 26 was subsequently shown to enhance memory in a Novel Object Recognition (NOR) behavioral study after a single dose of 0.03 mg/kg, and in a contextual fear conditioning (cFC) study after four QD doses of 0.01–0.03 mg/kg.